Effect of External Trainings of Employees on the Performance of Firms in the Soft Drink Industry in Kenya - Wakhu, Anne Masakhwe; Onyango, Maria; Monari, Fronica (International Journal of Social Sciences and Information Technology, 2024)
The soft drink industry in Kenya has been a significant contributor to the country's economy, and the performance of firms within this industry is crucial for economic growth and development. The impact of external training programs on employee performance within firms remains a critical and underexplored area of research. This study aims to investigate the extent to which external training initiatives influence the skill development, job satisfaction, and overall performance of employees within the Kenyan soft drink market. The data collected from Almasi Beverages Limited in Kisii County, Kenya, were analyzed using descriptive and inferential statistics to establish the relationship between the variables in this study. The results indicate that 68.5% of the firms observed a significantly positive impact on firm performance as a result of internal training programs in terms of employee acquiring new skills. Similarly, 64.85% of firms (64.85%) perceived a positive correlation between employee motivation, as influenced by external training, and firm performance. The regression analysis highlights the significant impact of Employee New Skills, Employee Motivation, Employee Job Satisfaction, and Employee Job Enrichment on organizational performance. These findings underscore the importance of these factors in driving organizational success and provide valuable insights for organizations seeking to enhance their performance through targeted interventions in employee skills, motivation, and job satisfaction. This research will contribute to a deeper understanding of the interplay between external training and organizational performance, guiding firms in their efforts to enhance employee capabilities and maintain a competitive edge in the dynamic Kenyan soft drink market.
Keywords: Employee Performance; External Training; Soft Drink Industry